Karakteristik Dan Simulasi Sistem Kontrol Hidrolik Pada Proses Pengepresan Biji Jaraks Kepyar (Ricinus Communis L.): Characteristic and Simulation of Hydraulic Control System onCastor Beans (Ricinus communis L.) Press Processing - Asih Priyati; Ansar Ansar; Sirajuddin Haji Abdullah (Jurnal Ilmiah Rekayasa Pertanian dan Biosistem, 2015)
This research aimed to study characteristic of hydraulic control system of castor beans pressing process. Experimental approach was conducted by using Complete Randomized Design to obtained relation between pressure’s variable and characteristics parameters of hydrolic control system and pressing process. Effet of pressure loading were investigated at 3, 5, 7, 9, and 11 kg, which replicated three times in order to obtained 15 units experiment. Characteristics parameters of hydraulic control system are pressure velocity, pressure, and pressure power. Pressing process parameters are distance of displacement, capacity of pressing process, and rendement. Result from this research showed that the hydraulic control system was able to transfered power using hydraulic oil in order to conduct pressing process. Higher loading pressure caused increasing pressure velocity, pressure, pressure power, pressing process capacity, and rendement. Whereas, lower loading pressure caused reduction on distance of displacement. Therefore, development on design is necessary to obtain optimal rendement quantity and further studies using extended pressure loading range is recommended.